Algumas generalizações do teorema clássico de Borsuk-Ulam - Morita, Ana Maria Mathias [UNESP] (2014)
The classic Borsuk-Ulam theorem states that if f : Sn ! Rn is a continuous map, then there exists a point x in the sphere such that f(x) = f(x). Since the publication, many generalizations of that result have been studied. Some generalizations consist in replacing either the domain (Sn;A), where A is the antipodal involution, by other free involution pair (X; T), or the target space Rn by more general topological spaces Y . In that case, we say that ((X; T); Y ) satisfies the Borsuk-Ulam property if given any continuous map f : X ! Y , there exists a point x in X such that f(x) = f(T(x)). In this work, we detail the proof of a classification result presented by Gonçalves in [6], that provides necessary and suficient conditions for a closed surface satisfy the Borsuk-Ulam property. We also show a detailed proof of a result presented by, Desideri, Pergher and Vendrúsculo in [3], that establishes an algebraic criterion for any topological space satisfy the Borsuk-Ulam property